The Impact of State-Society Relations on Anticorruption Agencies in Southern Africa - Toeba, Thato (Kyiv-Mohyla Law and Politics Journal, 2019)
Corruption remains a fundamental and intricate issue in public administration to date. It is featured constantly as one of the foremost discontents that societies around the globe have with the administration of public service and the resulting socio-economic problems.1 While anti-corruption law is extensively adopted in Southern Africa, the implementation of law has encountered deficiencies and challenges in tackling, especially grand corruption. This paper focuses on Anti-Corruption Agencies (ACAs) and their efficacy in controlling corruption in Southern Africa. It argues that the inability of ACAs to arrest corruption in Southern Africa is embedded inter-alia in the precarious state-society relations in the region which perpetuate the ambiguity for corruption and impede the formation of a moral consensus on anti-corruption law. The state, which is regarded generally as a trustworthy custodian of social progress is viewed by most domestic constituents as apathetic to social welfare with its political ambitions as anti-ethical to those of citizens. The paper proposes the analytical framework of Context, Resonance & Relevance (CRR) to assess the compatibility of Anti-Corruption Agencies (ACAs) in Southern Africa with domestic institutional contexts. In this model, context assesses ACA framework in relation to the domestic political environment and the extent to which it allows ACAs the capacity to function efficiently amidst competing political priorities. Resonance is concerned with the political relationship between the domestic society and the ACA and whether the operating framework sufficiently engages cultural codes specific in said society which De Sardan argues “banalise” or “justify” corruption. Relevance engages typologies of corruption in the region and whether reforms sufficiently are targeted at specific problems.